Recovery from chemically induced thymus atrophy starts with CD4- CD8- CD2high TcR alpha beta-/low thymocytes and results in an increased formation of CD4- CD8- TcR alpha beta high thymocytes. - Pieters, R H (1993)
Regeneration of the thymus was studied in rats that were treated with a single oral dose of the organotin compound di-n-butyltin dichloride (DBTC). After an initial maximum depletion of cortical BrdU+ thymocytes on day 2 after treatment, repopulation appeared to start on day 3 as indicated by an increased number of BrdU+ cells in the subcapsular region. On day 5, when thymocyte depletion was most pronounced, a relative increase of BrdU+ cells was observed all over the cortex. In comparison with controls, the thymoblast population on day 5 appeared to harbour increased numbers of CD4- CD8- and immature CD4- CD8+ CD53- thymoblasts, while the number of CD4+ CD8+ blasts had decreased. In comparison with day 3, however, the number of CD4+ CD8+ blasts had increased again. Results together have been interpreted as indicative for thymus regeneration starting from CD4- CD8- blasts which differentiate to immature CD4- CD8+ and then to CD4+ CD8+ blasts. Further characterization revealed that the majority of the CD4- CD8- and CD4- CD8+ CD53- blasts expressed high levels of CD2 and no or low levels of T-cell receptor (TcR) alpha beta. The high expression of CD2 on repopulating thymoblasts may be an additional indication of their activated state and for a role of interaction with the ligand LFA-3 on thymic epithelial cells during this phase of thymocyte differentiation. The number of CD4- CD8- TcR alpha beta high cells was increased on day 5 after dosing. The origin of this population and the possible implication of its development during thymus regeneration after chemically induced thymus atrophy are discussed.